Strategy of Maintaining Values Sasak Local Culture through Cultural Tourism in the Age of Globalization (Case Study in Sade Traditional Village) - Alhadika, Muhammad; Suryono, Hasan; Nuryadi, Muhammad Hendri (Budapest International Research and Critics University, 2021)
This article reveals the strategy of cultural tourism in maintaining the local cultural values of the Sasak tribe in the era of globalization, the existence of local culture needs to be maintained and maintained so that it is not displaced by foreign cultures through world developments. In implementing this strategy, of course, it must be supported by a group of people, especially local residents so that this strategy is able to run as it should. The cultural tourism strategy is used because this strategy is quite good at attracting tourists to know about the local culture found in each region.